ANALISIS PEMILIHAN KARTU GSM PRABAYAR DI KALANGAN MAHASISWA DENGAN PENDEKATAN RANTAI MARKOV (Studi Kasus pada Mahasiswa Universitas Bunda Mulia, Jurusan Manajemen, Semester 8) - Indra Indra; Lanang Diayudha (Universitas Bunda Mulia, 2017)
The many variety of GSM card and services enables the customers to change brands easily. This has caused a tighter competition between the brands. In order to face the competition, GSM operators need to understand the customers’ perception and judgment on the preference scale toward the atribute of the products and services. GSM card operators also need to understand the brand switching pattern and its competitior position in analysing the market today or in the future. By the analyses, the operator hopes to acquired some description of their position and product situation among the tight competition between4 operators. The description can then be used as input in determining the marketing strategies for the future. The objects in this research are analyzed using Markov’s chain method on brand switching. The analysis on customer’s judgments on the product attributes and services is aided by the use of descriptive statistics. The case study is performed on the 8th semester students of Bunda Mulia University, majoring in Management. The population is 105 students. The research method is by using survey and the type of research is descriptive research. The data collecting technique is through the use of questionnaire and literary review. The results shows that the source of reference of the customer’s choice which is 3.81% from the event, 12.38% from families, 29.52 from commercials, 45.71% from friends, and 8.57% from other unspecified sources. The prediction of the market from the five operators in consequential orders are (0.0695, 0.6401, 0.0295, 0.1207, 0.1402), and the prediction of equilibrium moment are (0.0218, 0.5805, 0.0264, 0.117, 0.2543).The biggest market share is owned by XL which is 64.01%, and the smallest is by mentari with the share of 2.95%. The biggest sorce of reference for the students in choosing operators is from promotion events with the percentage of 30.81% and from friends is only 19.88%. Looking at this result it can be suggested that operators should increase their services and increase their promotion events in gaining the market share of GSM users. Keyword : GSM cards, brand switching, Markov’s chain, market share